Circulating heat treatment method for improving performance of TC4 titanium alloy annular component

By using a combination of cyclic heat treatment and 500°C aging treatment in the additive manufacturing TC4 titanium alloy ring member, a two-state structure of sheet-like α phase and spheroidized α phase is formed, which solves the problem of the intermediate-isometric crystal structure component of additive manufacturing. The problem of uniformity significantly improves the corrosion resistance and hardness of the components.

CN119287293APending Publication Date: 2025-01-10SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415941.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the additive manufacturing process, the TC4 titanium alloy annular member has uneven structure components due to rapid heating and cooling of the deposited layer, which cannot meet the service requirements.

Method used

The cyclic heat treatment method is adopted, and the specific steps include 19 cycle heat treatments within the temperature range of 850°C to 950°C, and combined with the aging treatment of 500°C, forming a two-state structure composed of a sheet-like α phase and a spheroidized α phase.

Benefits of technology

The performance of TC4 titanium alloy annular components is significantly improved, especially corrosion resistance and hardness. The average Vickers hardness is increased by 67.02%, the corrosion current density is the lowest, and the structure is more uniform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287293A_ABST
    Figure CN119287293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of a cyclic heat treatment method for improving the performance of a TC4 titanium alloy annular component, and discloses a cyclic heat treatment method for improving the performance of the TC4 titanium alloy annular component, which comprises the following steps: 1, cyclic heat treatment: heating a TC4 titanium alloy sample to 940-950 DEG C from room temperature for T < heating >, cooling to 840-850 DEG C at the cooling speed of VC, and preserving heat for 2-3 hours; the temperature is increased to 940-950 DEG C at the temperature increasing speed of VR, the process is a cycle, the treatment time is T1, heat treatment is cycled for n times, and air cooling is conducted to the room temperature after treatment; the TC4 titanium alloy sample obtained after the first step is cooled to the room temperature and then immediately enters a furnace, the temperature of the TC4 titanium alloy sample is increased to 500-600 DEG C for aging treatment, the aging treatment time is T2, and the TC4 titanium alloy sample is air-cooled to the room temperature after being treated. According to the method, the microstructure of a component obtained through additive manufacturing can be improved by adjusting heat treatment process parameters, the performance of the component is improved, and the corrosion resistance is improved to a great extent. The economical efficiency is good, and the adjustable range is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment methods for arc additively manufactured TC4 titanium alloy annular components, and specifically to a cyclic heat treatment method for improving the performance of TC4 titanium alloy annular components. Background Art

[0002] Titanium alloys have high specific strength, low density, high temperature resistance, good corrosion resistance, good biocompatibility, and excellent comprehensive performance. They are widely used in aerospace, marine, medical and military fields. TC4 titanium alloy is a typical α+β type titanium alloy. The content and morphology of α phase and β phase can be changed through deformation heat treatment, and it has good strength and plasticity matching.

[0003] Additive manufacturing (AM), also known as 3D printing technology, can effectively improve the utilization rate of materials and realize the rapid manufacturing of complex structural parts. It has broad application prospects in the fields of aerospace, shipbuilding, medical, chemical industry, etc. Cold metal transfer (CMT) is a welding technology with low heat input, which has the advantages of no spatter, good bridging ability, uniform forming, low heat input, and small deformation. However, in the process of additive manufacturing, the rapid heating and cooling of the deposited layer and repeated thermal cycles cause the equiaxed crystal structure to be remelted many times, resulting in uneven tissue composition and unable to meet the service requirements. In order to solve the above problems, we propose a cyclic heat treatment method to improve the performance of TC4 titanium alloy ring components. Summary of the invention

[0004] The object of the present invention is to provide a cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components,

[0006] Step 1: Cyclic heat treatment: The heating time of the TC4 titanium alloy sample is T rise, from room temperature to 940℃~950℃, cooled to 840℃~850℃ at a cooling rate of VC, and then heated to 940℃~950℃ at a heating rate of VR. This process is one cycle, the treatment time is T1, the cyclic heat treatment is n times, and air cooling is performed to room temperature after treatment;

[0007] Step 2: Aging treatment: After the TC4 titanium alloy sample in step 1 is cooled to room temperature, it is immediately put into the furnace, and the TC4 titanium alloy sample is heated to 500°C to 600°C for aging treatment. The aging treatment time is T2, and then air-cooled to room temperature.

[0008] Preferably, the chemical composition of the TC4 titanium alloy by weight percentage is as follows:

[0009] Al: 6.00 wt.%~6.05 wt.%;

[0010] V: 3.90wt.%~4.05wt.%;

[0011] Fe: 0.14wt.%~0.18wt.%;

[0012] C: 0.02wt.%~0.08wt.%;

[0013] N: 0.01wt.%~0.02wt.%;

[0014] O: 0.09wt.%~0.12wt.%;

[0015] Ti margin.

[0016] Preferably, the cyclic heat treatment is carried out in a temperature range of 850°C to 950°C.

[0017] Preferably, the VC is 2.5°C / min; the VR is 5°C / min.

[0018] Preferably, in step 1, n is 19.

[0019] Preferably, the T1 is 1 h; the T2 is 3 h.

[0020] Preferably, the T 升 For 2h.

[0021] Compared with the prior art, the beneficial effects of the present invention are: the cyclic heat treatment method for improving the performance of TC4 titanium alloy annular components can improve the microstructure of the components obtained by additive manufacturing by adjusting the heat treatment process parameters, thereby improving the performance of the components and greatly improving the corrosion resistance. It has good economic efficiency and a large adjustable range. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the movement path of the welding gun on the annular component in the additive manufacturing of the present invention;

[0023] Figure 2 It is a schematic diagram of the swing trajectory of the welding gun on the annular component in the additive manufacturing of the present invention;

[0024] Figure 3 This is the OM morphology of the unheat-treated sample of TC4 titanium alloy in Comparative Example 1 of the present invention;

[0025] Figure 4The SEM morphology of the unheat-treated sample of TC4 titanium alloy in Comparative Example 1 of the present invention at 30 μm;

[0026] Figure 5 The SEM morphology of the TC4 titanium alloy unheat-treated sample at 5 μm in Comparative Example 1 of the present invention;

[0027] Figure 6 This is the OM morphology of the TC4 titanium alloy heat-treated sample in Comparative Example 2 of the present invention;

[0028] Figure 7 The SEM morphology of the TC4 titanium alloy heat-treated sample at 30 μm in Comparative Example 2 of the present invention;

[0029] Figure 8 This is the SEM morphology of the TC4 titanium alloy heat-treated sample at 5 μm in Comparative Example 2 of the present invention;

[0030] Fig. 9 It is a temperature variation curve diagram of the TC4 titanium alloy heat treatment sample in Comparative Example 2 of the present invention;

[0031] Fig.10 It is a temperature variation curve diagram of the TC4 titanium alloy heat treatment sample in Comparative Example 3 of the present invention;

[0032] Fig.11 This is the OM morphology of the TC4 titanium alloy heat-treated sample in Comparative Example 4 of the present invention;

[0033] Fig.12 The SEM morphology of the TC4 titanium alloy heat-treated sample at 30 μm in Comparative Example 4 of the present invention;

[0034] Fig.13 This is the SEM morphology of the TC4 titanium alloy heat-treated sample at 5 μm in Comparative Example 4 of the present invention;

[0035] Fig.14 It is a temperature variation curve diagram of the TC4 titanium alloy heat treatment sample in Comparative Example 4 of the present invention;

[0036] Fig.15 This is the OM morphology of the TC4 titanium alloy heat-treated sample in Example 1 of the present invention;

[0037] Fig.16 The SEM morphology of the TC4 titanium alloy heat-treated sample at 30 μm in Example 1 of the present invention;

[0038] Fig.17 The SEM morphology of the TC4 titanium alloy heat-treated sample at 5 μm in Example 1 of the present invention;

[0039] Fig.18It is a temperature variation curve diagram of the TC4 titanium alloy heat treatment sample in Example 1 of the present invention;

[0040] Fig.19 OM morphology of the TC4 titanium alloy heat-treated sample in Example 2 of the present invention;

[0041] Fig. 20 The SEM morphology of the TC4 titanium alloy heat-treated sample at 30 μm in Example 2 of the present invention;

[0042] Fig.21 The SEM morphology of the TC4 titanium alloy heat-treated sample at 5 μm in Example 2 of the present invention;

[0043] Fig. 22 It is a temperature variation curve diagram of the TC4 titanium alloy heat treatment sample in Example 2 of the present invention;

[0044] Fig.23 This is a table of polarized corrosion parameters of Examples 1 and 2 of the present invention and Comparative Examples 1, 2, and 4;

[0045] Fig.24 The average Vickers hardness distribution curves of Examples 1 and 2 of the present invention and Comparative Examples 1, 2 and 4 after different heat treatments;

[0046] Fig.25 These are the Tafel curves of Examples 1 and 2 of the present invention and Comparative Examples 1, 2 and 4 after different heat treatments.

[0047] In the figure: 1-starting and ending points, 2-second point, 3-third point, 4-fourth point, 5-fifth point, 6-sixth point. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] See also Figure 1 , Figure 2The arc additive manufacturing experimental substrate used in the present invention is a TC4 titanium alloy plate with a substrate size of 250mm×50mm×4mm, and a finished TC4 welding wire with a diameter of 1.2mm is used as the forming raw material. The titanium alloy program in the cold metal transition technology is adopted to carry out titanium alloy arc additive manufacturing. The shielding gas is 99.99% high-purity argon. The additive manufacturing system built in the experiment is a complete cold metal transition welding system consisting of a Fronius CMT TPS 4000 welding machine and a Kawasaki BA006N six-axis welding robot. The specific connection methods are all existing technologies and will not be repeated here.

[0050] The chemical composition of the TC4 titanium alloy by weight percentage is as follows:

[0051] Al: 6.00wt.%~6.05wt.%; V: 3.90wt.%~4.05wt.%; Fe: 0.14wt.%~0.18wt.%; C: 0.02wt.%~0.08wt.%; N: 0.01wt.%~0.02wt.%; O: 0.09wt.%~0.12wt.%; Ti balance.

[0052] Manufacturing method: The titanium alloy program in the cold metal transition technology is used to perform arc additive manufacturing of titanium alloy. The wire feeding speed is 7m / min, the welding speed is 30cm / min, the gas flow rate is 25L / min, the swing pattern is a Z-shaped symmetrical swing, the swing amplitude is 4mm, and the frequency is 4Hz. Based on the shape of the TC4 titanium alloy annular component manufactured by arc additive manufacturing, the motion trajectory of the welding gun on the annular component is determined, and a closed path is formed by the starting point, five midpoints, and the end point. The starting and ending points 1 to the second point 2 are straight lines with a length of 13cm; the second point 2 to the third point 3 is a 1 / 4 circle with a radius of 1.5cm; the third point 3 to the fourth point 4 is a 1 / 4 circle with a radius of 1.5cm; the fourth point 4 to the fifth point 5 is a straight line with a length of 13cm; the fifth point 5 to the sixth point 6 is a 1 / 4 circle with a radius of 1.5cm; the sixth point 6 to the starting and ending points 1 is a 1 / 4 circle with a radius of 1.5cm. The components were prepared by reciprocating motion, and the end point of the previous layer was the starting point of the next layer, that is, one layer was prepared from the straight part, and the other layer was prepared from the arc part. The program to be used for each layer was set in the teach pendant, the Z-axis offset was 4mm for each layer, the interlayer cooling time was set to 2min, and a total of 11 layers were stacked.

[0053] It should be noted here that the manufacturing methods and alloy compositions of the components of Example 1, Example 2 and Comparative Examples 1, Comparative Example 2 and Comparative Example 4 are all consistent.

[0054] See also Fig.15 , Fig.16 , Fig.17 , Fig.18 For Example 1:

[0055] Cyclic heat treatment + aging treatment: The TC4 titanium alloy sample is first heated from room temperature to 950℃ for 2h. When it is heated to 950℃, it is cooled to 850℃ at a cooling rate of 2.5℃ / min. When it is cooled to 850℃, it is heated to 950℃ at a heating rate of 5℃ / min. This process is one cycle, and the treatment time is 1h. The cyclic heat treatment is performed 19 times in the temperature range of 850℃ to 950℃, and the treatment time is 19h. After the heat treatment, it is air-cooled to room temperature. After the cyclic heat treatment, the TC4 titanium alloy sample is cooled to room temperature and then put into the furnace and heated to 500℃ for aging treatment. The aging treatment time is 3h, and it is air-cooled to room temperature after treatment. During the heating process of cyclic heat treatment, the lamellar α phase transforms into the β phase. During the cooling process, the spheroidized α phase is transformed due to slow cooling. After 19 cycles of heat treatment plus aging treatment, the spheroidization of the α phase is observed at the grain boundary. The aspect ratio of the lamellar α phase is reduced, the sphericity is higher, more spheroidized α phase is transformed, and the distribution is more uniform. The final organization is composed of lamellar α phase and spheroidized α phase.

[0056] The above samples were ground and polished, and the TC4 titanium alloy samples were corroded using Kroll reagent (HF:HCl:H2O=1:2:50) for 10 seconds. The samples were washed with deionized water and dried with compressed air before observation.

[0057] See also Fig.19 , Fig. 20 , Fig.21 , Fig. 22 For Example 2:

[0058] Different from Example 1, the aging treatment in Example 2 is heated to 600°C.

[0059] Cyclic heat treatment + aging treatment: The TC4 titanium alloy sample was first heated from room temperature to 950℃ for 2h. When it was heated to 950℃, it was cooled to 850℃ at a cooling rate of 2.5℃ / min. When it was cooled to 850℃, it was heated to 950℃ at a heating rate of 5℃ / min. This process was one cycle, and the treatment time was 1h. The cyclic heat treatment was performed 19 times in the temperature range of 850℃ to 950℃, and the treatment time was 19h. After the heat treatment, it was air-cooled to room temperature. After the cyclic heat treatment, the TC4 titanium alloy sample was cooled to room temperature and then heated to 600℃ in the furnace for aging treatment. The aging treatment time was 3h, and it was air-cooled to room temperature after treatment. In this process, the fine needle-shaped α′ was transformed into lamellar α phase and some spheroidized α phase. Some lamellar α phases were coarsened, and there were more spheroidized α phases, but the organization was still dominated by lamellar α phase.

[0060] See also Figure 3 , Figure 4 , Figure 5For comparative example 1:

[0061] As-deposited structure: Arc additive manufacturing TC4 titanium alloy specimen without heat treatment, the base structure fine needle-shaped martensite and lamellar α phase exist in β grains, see Figure 3 .

[0062] See also Figure 6 , Figure 7 , Figure 8 , Fig. 9 For comparative example 2:

[0063] Solution + cyclic heat treatment: The TC4 titanium alloy sample was heated from room temperature to 1025℃ for 2h, kept at this temperature for 1h, and air-cooled to room temperature. Then the sample was heated from room temperature to 950℃ for 2h, cooled to 850℃ at a cooling rate of 2.5℃ / min, and then heated to 950℃ at a heating rate of 5℃ / min. This process was one cycle, and the treatment time was 1h. The sample was heat-treated 19 times in the temperature range of 850℃ to 950℃, and the treatment time was 19h. After the heat treatment, the sample was air-cooled to room temperature. After the heat treatment, the fine needle-shaped martensite undergoes a phase transformation, transforming into a lamellar α phase and a small amount of spheroidized α phase, and a small amount of lamellar α is coarsened.

[0064] See also Fig.10 For comparative example 3:

[0065] Heat treatment: The TC4 titanium alloy sample was heated from room temperature to 940°C for 2h, isothermally maintained at 940°C for 19h, and air-cooled to room temperature after treatment. After heat treatment, a small amount of lamellar α phase began to break and had a tendency to spheroidize, but there was almost no spheroidized α phase. This is the prior art, and the experimental data will not be repeated.

[0066] See also Fig.11 , Fig.12 , Fig.13 , Fig.14 For comparative example 4:

[0067] Cyclic heat treatment: TC4 titanium alloy sample TC4 titanium alloy sample was heated from room temperature to 950℃ for 2h, cooled to 850℃ at a cooling rate of 2.5℃ / min, and then heated to 950℃ at a heating rate of 5℃ / min. This process was one cycle, and the treatment time was 1h. The cyclic heat treatment was performed 19 times in the temperature range of 850℃~950℃, and the treatment time was 19h. After the heat treatment, it was air-cooled to room temperature. After the heat treatment, the fine needle-shaped α′ was transformed into a lamellar α phase and a small amount of spheroidized α phase.

[0068] Comparative Example 1, Comparative Example 2, Comparative Example 4 and Example 1 and Example 2 were subjected to Vickers hardness measurement. The measurement results are shown in Fig.24. Compared with the average Vickers hardness of 334.8 HV in Comparative Example 1, the average Vickers hardness of Comparative Example 2 is 529.1 HV, an increase of 58.03%, and the average Vickers hardness of Example 2 is 541.3 HV, an increase of 61.68%. The average Vickers hardness of Comparative Example 4 is 512.2 HV, an increase of 52.99%. The average Vickers hardness of Example 1 is 586.3 HV, an increase of 67.02%. The hardness of Comparative Example 2, Comparative Example 4, Example 1, and Example 2 has been improved, but the cyclic heat treatment in the temperature range of 850°C to 950°C adopted in Example 1, combined with the aging treatment at 500°C for 3h, has more spheroidized α phase, more uniform structure, and the most obvious improvement in hardness. The average Vickers hardness value of Example 2 is more closely distributed, less fluctuating, and more stable.

[0069] The Tafel curves of Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 4 are as follows: Fig.25 As shown, the trend of all curves is basically the same. After calculation, the corrosion potential and corrosion current density refer to Fig.23 The TC4 titanium alloy sample of Example 1, which was subjected to cyclic heat treatment in the temperature range of 850°C to 950°C and then aging treatment at 500°C, had the lowest corrosion current density and lower corrosion rate, indicating that its corrosion resistance was improved.

[0070] It was observed that the OM structures of Example 1, Example 2 and Comparative Example 1, Comparative Example 2 and Comparative Example 4 were as follows: Figure 3 , Figure 6 , Fig.11 , Fig.15 , Fig.19 As shown, the formation of lamellar α and spheroidized α phases can be observed. The SEM structures of Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 4 are as follows: Figure 4 , Figure 5 , Figure 7 , Figure 8 , Fig.12 , Fig.13 , Fig.16 , Fig.17 , Fig. 20 , Fig.21 shown.

[0071] It should be noted here that the plot of the logarithm of the current density and the overpotential is called a Tafel plot, and the straight line obtained therein is called a Tafel curve. This is the prior art and will not be described in detail here.

[0072] See also Fig.23 , Fig.24Most of the existing technologies solve the alloy hardness requirements by cyclic heat treatment to improve the hardness of the obtained alloy as much as possible. However, the present application can greatly improve the corrosion resistance of the TC4 titanium alloy sample by combining the step 1: cyclic heat treatment with the step 2: aging treatment.

[0073] Working principle:

[0074] A heat treatment method for improving the performance of an arc additively manufactured TC4 titanium alloy annular component, wherein the additively manufactured TC4 titanium alloy component is heat treated by a cyclic heat treatment plus aging treatment method to obtain a dual-state structure consisting of a lamellar α phase and a spheroidized α phase, and the operation steps are as follows:

[0075] (1) A TC4 titanium alloy annular component was prepared by arc additive manufacturing. The component was 16 cm long, 1.5 cm in radius, and 4.3 cm in height.

[0076] (2) Cyclic heat treatment: The TC4 titanium alloy sample was subjected to cyclic heat treatment in the temperature range of 850°C to 950°C for 19 h.

[0077] (3) Aging treatment: The aging treatment temperature is 500°C and the treatment time is 3h.

[0078] During the arc additive manufacturing process, the deposited layer is rapidly heated and cooled, and the equiaxed crystal structure formed undergoes multiple remelting, resulting in uneven tissue composition, and the performance does not meet the service requirements. Through the method of cyclic heat treatment, the tissue composition of the components manufactured by arc additive manufacturing can be improved, so that the fine needle-shaped α′ martensite is transformed into a dual-state structure composed of lamellar α phase and spheroidized α phase. After aging treatment at 500℃ for 3h, the structure is more uniform. This dual-state microstructure has high strength in TC4 titanium alloy and can effectively improve the performance of TC4 titanium alloy annular components manufactured by arc additive manufacturing. Different from the prior art, after a combination of cyclic heat treatment and aging treatment, the sphericity is higher, more spheroidized α phase can be obtained, the tissue distribution is uniform, the average Vickers hardness of TC4 titanium alloy is increased to 586.3HV, an increase of 67.02%, and the corrosion current density is the lowest, at 0.147μA·cm -2 , hardness and corrosion resistance have been improved. The performance of TC4 titanium alloy ring components has been further improved, providing new ideas for the heat treatment method of TC4 titanium alloy, and making additive manufacturing of TC4 titanium alloy components widely used in practice.

[0079] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0080] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components, characterized in that: Step 1: Cyclic heat treatment: The heating time of the TC4 titanium alloy sample is T rise, from room temperature to 940℃~950℃, cooled to 840℃~850℃ at a cooling rate of VC, and then heated to 940-950℃ at a heating rate of VR. This process is one cycle, the treatment time is T1, the cyclic heat treatment is n times, and air cooling is performed to room temperature after treatment; Step 2: Aging treatment: After the TC4 titanium alloy sample in step 1 is cooled to room temperature, it is immediately put into the furnace, and the TC4 titanium alloy sample is heated to 500°C to 600°C for aging treatment. The aging treatment time is T2, and then air-cooled to room temperature.

2. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components according to claim 1, characterized in that: The chemical composition of the TC4 titanium alloy by weight percentage is as follows: Al: 6.00 wt.%~6.05 wt.%; V: 3.90wt.%~4.05wt.%; Fe: 0.14wt.%~0.18wt.%; C: 0.02wt.%~0.08wt.%; N: 0.01wt.%~0.02wt.%; O: 0.09wt.%~0.12wt.%; Ti margin.

3. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components according to claim 1, characterized in that: The V C is 2.5℃ / min; the V R is 5℃ / min.

4. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components according to claim 1, characterized in that: In the step 1, n is 19.

5. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components according to claim 1, characterized in that: The T1 is 1 h; the T2 is 3 h.

6. A cyclic heat treatment method for improving the performance of TC4 titanium alloy ring components according to claim 1, characterized in that: The T 升 For 2h.